Identifying appropriate candidates for long-acting antiretroviral therapy: findings from a survey of health care providers in the ATLAS-2M trial. Issue 4 (11th October 2020) - Murray, Miranda; Kerrigan, Deanna; Hudson, Krischan J.; Walters, Nicola; Karver, Tahilin Sanchez; Mantsios, Andrea; Galai, Noya
Abstract : Introduction: Recent results from Phase 3 clinical trials with cabotegravir (CAB) and rilpivirine (RPV) long-acting (LA) have shown that a monthly regimen is non-inferior to daily oral antiretroviral therapy (ART). Additional insights are necessary to prepare for LA ART roll-out, including identifying the appropriate patients. Methods: Within the ATLAS-2M trial, an online survey was administered to 329 health care providers (HCPs) in 13 countries. Multivariate logistic regression was conducted to identify factors associated with providers considering a greater proportion of patients as appropriate LA ART candidates. Results: Forty-seven percent of HCPs believed that "some" patients (25–50%) would be appropriate while nearly one-quarter of HCPs (23%) felt that "many" patients (more than 50%) would be appropriate candidates for LA ART. Providers in the African region had a greater odds of identifying a greater proportion of their patients as appropriate candidates (AOR 8.97; p < 0.001) vs. other regions. Nurses/physician assistants and research staff/pharmacists had a higher odds of perceiving a greater proportion of their patients as appropriate candidates vs. physicians, respectively (AOR 3.42 p < 0.001; AOR 2.48; p = 0.19). Providers who had experience transitioning patients from LA to oral ART had a higher odds of reporting that more of their patients would be appropriate candidates (AOR 1.64; p = 0.008) vs. those without experience. Conclusion: A significant proportion of providers reported that many of their patients would be appropriate candidates for LA ART. To optimize roll-out after regulatory approval, it is important to support providers with tools to help identify patients who would most benefit from this option.